Regulasi Emosi Pada Pengikut Tarekat Syattariyah - Bagus Adi Nugroho; Bagus Wicaksono; Rini Setyowati (UNS Press, 2022)
Abstract. Modern life’s pressure makes people experience emotional distress. However, this can be faced by the followers of the Syattariyah Order through the teachings that aim to achieve the insanul kamil’s condition. This study aims to describe the emotional regulation of followers of the Tarekat Syattariyah. This study uses a qualitative research method with a phenomenological study design. The subjects were selected using a purposive sampling technique. There are two subjects who are followers of the Syattariyah Order, namely BW (55 years) and WM (53 years). Data collection methods used are curriculum vitae, interviews, and observations. Data analysis used interpretive phenomenological analysis method. The subject's emotional regulation process focuses on the stages of attention deployment and Cognitive Change. In attention deployment stages, subjects uses the strategy of heart rhythm’s observing which accompanied by remembrance. Therefore, in the Cognitive Change stage, the Syattariyah’s followe congregation use an intuitive or affirmative reassessment strategy. In the Response Modulation stage, the subject uses an expressive suppression strategy or physical activity. Emotional awareness and religiosity supported by Sufism are the biggest factors that influence the emotion regulation process of tarekat followers. Through this process, the emotional regulation of the followers runs adaptively.